2016
DOI: 10.1210/en.2015-1297
|View full text |Cite
|
Sign up to set email alerts
|

Low Oxygen Tension Modulates the Insulin-Like Growth Factor-1 or -2 Signaling via Both Insulin-Like Growth Factor-1 Receptor and Insulin Receptor to Maintain Stem Cell Identity in Placental Mesenchymal Stem Cells

Abstract: Placental mesenchymal stem cells (PMSCs) are readily available multipotent stem cells for potential use in regenerative therapies. For this purpose, PMSCs must be maintained in culture conditions that mimic the in vivo microenvironment. IGFs (IGF-1 and IGF-2) and oxygen tension are low in the placenta in early gestation and increase as pregnancy progresses. IGFs bind to two receptor tyrosine kinases, the IGF-1 receptor (IGF-1R) and the insulin receptor (IR), and their hybrid receptors. We hypothesized that IGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…For a more detailed review on insulin and IGF receptor signaling in neural stem cells, please see Ziegler et al (2015) [92]. We verified the role of IR-A in PMSC, where we showed an elevated expression level of IR-A versus IR-B; and both IGF-1 and IGF-2 promote increased proliferation and self-renewal with a requirement that both IGF-1R and IR must be present [80]. Although IGF-1R and IR can form hybrid receptors, the role of hybrid receptor in maintaining stem cell fate (ESCs or MSCs) and pluripotency is yet to be confirmed.…”
Section: The Role Of Igfs In Msc Multipotency and Self-renewalsupporting
confidence: 71%
See 3 more Smart Citations
“…For a more detailed review on insulin and IGF receptor signaling in neural stem cells, please see Ziegler et al (2015) [92]. We verified the role of IR-A in PMSC, where we showed an elevated expression level of IR-A versus IR-B; and both IGF-1 and IGF-2 promote increased proliferation and self-renewal with a requirement that both IGF-1R and IR must be present [80]. Although IGF-1R and IR can form hybrid receptors, the role of hybrid receptor in maintaining stem cell fate (ESCs or MSCs) and pluripotency is yet to be confirmed.…”
Section: The Role Of Igfs In Msc Multipotency and Self-renewalsupporting
confidence: 71%
“…MSCs isolated from different tissues, such as bone marrow, adipose tissue, placental chorionic villi, and fetal membranes, express and secrete IGF-1 and/or IGF-2 in vitro [8083]. It was shown that ectopic IGF-1 expression in MSCs enhances their proliferation with lower apoptosis [84].…”
Section: The Role Of Igfs In Msc Multipotency and Self-renewalmentioning
confidence: 99%
See 2 more Smart Citations
“…Various differentiation inducing factors such as stromal cell-derived factor-1 (SDF-1), insulin like growth factor-1 and granulocyte colony-stimulating factor, play a key role in stem cell directional migration and differentiation (4,5). However, previous studies focused on the differentiation-inducing factor promoting the stem cell therapy effect (6,7).…”
Section: Introductionmentioning
confidence: 99%